Unconventional monetary policies, with a focus on quantitative easing - Marc Lavoie; Brett Fiebiger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
This article distinguishes between credit easing policies and quantitative easing (QE) policies. The authors argue that there are two broad transmission mechanisms associated with quantitative easing: the Friedmanian mechanism, which is based on the theory of the money multiplier and the fractional-reserve banking system; and the Keynesian mechanism, advocated by Keynes in 1930, which relies on its impact on interest rates. The article also deals with the likely consequences of various incarnations of QE policies: QE done with banks, QE done with non-banks, QE for the people, Corbyn's people's QE and green QE. This is done by looking at the impact of these policies on the balance sheets of banks, private agents, the central bank and the government, and on their consequences for the fiscal balance of the government when taking into account the profits that are distributed by the central bank to the government. It is concluded that accounting tricks cannot modify reality.
Keywords: E51; E58; E63; 330; quantitative easing; QE for the people; people's QE; green QE; fiscal policy